Tradeoff between Assessment and Control of Aquatic Invasive Species: A Case Study of Sea Lamprey Management in the St. Marys River. (2nd January 2016) - Robinson, Jason M.; Wilberg, Michael J.; Adams, Jean V.; Jones, Michael L.
Abstract: Allocating resources between the gathering of information to guide management actions and implementing those actions presents an inherent tradeoff. This tradeoff is evident for control of the Sea Lamprey Petromyzon marinus in the St. Marys River, connecting Lakes Huron and Superior and a major source of parasitic Sea Lampreys to Lake Huron and northern Lake Michigan. Larval Sea Lampreys in the St. Marys River are controlled through the application of Bayluscide, which is applied to areas of high larval density. Bayluscide applications are guided with an annual deepwater electrofishing survey to estimate larval Sea Lamprey density at relatively fine spatial scales. We took a resampling approach to describe the effect of sampling intensity on the success of the larval Sea Lamprey management program and explicitly incorporated the economic tradeoff between assessment and control efforts to maximize numbers of larvae killed in the St. Marys River. When no tradeoff between assessment and control was incorporated, increasing assessment always led to more larvae killed for the same treatment budget. When the tradeoff was incorporated, the sampling intensity that maximized the number of larvae killed depended on the overall budget available. Increased sampling intensities maximized effectiveness under medium to large budgets (US0.4 to 2.0 million), and intermediate sampling intensities maximized effectiveness under low budgets. Sea Lamprey control actions based on assessment information outperformed those that were implemented with no assessment under all budget scenarios. Received March 26, 2015; accepted September 30, 2015